Analysis of the baseline performance of five UK lung cancer screening programmes. (November 2021) - Balata, Haval; Ruparel, Mamta; O'Dowd, Emma; Ledson, Martin; Field, John K.; Duffy, Stephen W.; Quaife, Samantha L.; Sharman, Anna; Janes, Sam; Baldwin, David; Booton, Richard; Crosbie, Philip A.J.
Highlights: Minimising harms is critical in lung cancer screening implementation. We report cumulative real-world lung cancer screening data from the UK. Reported harms, including false positive and benign resection rates, are low. Outcomes are comparable to, and in some aspects superior to, published RCTs. Abstract: Introduction: Low-dose CT (LDCT) screening reduces lung cancer specific mortality. Several countries, including the UK, are evaluating the clinical impact and cost-effectiveness of LDCT screening using the latest evidence. In this paper we report baseline screening performance from five UK-based lung cancer screening programmes. Methods: Data was collected at baseline from each screening programme. Measures of performance included prevalence of screen detected lung cancer, rate of surveillance imaging for indeterminate findings and surgical resection rates. Screening related harms were assessed by measuring false positive rates, number of invasive tests with associated complications in individuals without lung cancer and benign surgical resection rates. Results: A total of 11, 148 individuals had a baseline LDCT scan during the period of analysis (2011 to 2020). Overall, 84.7% (n = 9, 440) of baseline LDCT scans were categorised as negative, 11.1% (n = 1, 239) as indeterminate and 4.2% (n = 469) as positive. The prevalence of screen detected lung cancer was 2.2%, ranging between 1.8% and 4.4% for individual programmes. The surgical resection rate was 66% (range 46% to 83%) and post-surgical 90-day mortality for those with lung cancer 1.2% (n = 2/165). The false positive rate was 2% (n = 219/10, 898) and of those with a positive result, one in two had lung cancer diagnosed (53.3%). An invasive test was required in 0.6% (n = 61/10, 898) of screening attendees without lung cancer; there were no associated major complications or deaths. The benign surgical resection rate was 4.6% (n = 8/173), equating to 0.07% of the screened population. Discussion: The performance of UK-based lung cancer screening programmes, delivered within or aligned to the National Health Service, compares favourably to published clinical trial data. Reported harms, including false positive and benign surgical resection rates are low. Ongoing monitoring of screening performance is vital to ensure standards are maintained and harms minimised.